Chronic pelvic pain syndrome in women of reproductive age: An observational cohort clinical ultrasound study - E. S. Dukhanina; E. V. Enkova; K. I. Obernikhin; A. A. Pashkova; N. V. Strahova; V. V. Enkova; V. A. Ivanenko (Кубанский научный медицинский вестник, 2024)
Background. The annual number of new cases of chronic pelvic pain syndrome in women of reproductive age is increasing worldwide. The high prevalence of this condition among the able-bodied female population leads to higher state expenditures on the treatment of this category of patients. New methods of diagnosis and early prophylaxis contribute to reducing economic burden associated with chronic pelvic pain syndrome in women and improving health of the female population as a fundamental demographic factor.Objectives. To determine somatic, obstetric-gynecological, anatomical, and psycho-emotional predictors of chronic pelvic pain syndrome.Methods. An observational cohort clinical and ultrasound study involved 60 patients of reproductive age. The study was conducted on the basis of the clinic for women, Voronezh City Outpatient Clinic No. 1 — clinical base of the Department of Obstetrics and Gynecology No. 2, Voronezh State Medical University named after N. N. Burdenko, Russia. According to clinical and laboratory data, the participants were divided into 2 groups. Group 1 (n = 30) included women of reproductive age without clinical manifestations of chronic pelvic pain syndrome; Group 2 (n = 30) enrolled women of reproductive age clinically diagnosed with chronic pelvic pain.Results. The mean age of the study participants in the main group comprised 27.4 ± 6.30 and 26.3 ± 7.25 years in the control group, p > 0.05. Diseases of gastrointestinal tract, endocrine, cardiovascular, musculoskeletal and urinary systems, as well as neurocirculatory and vegetative disorders prevailed in the structure of somatic pathology in the main group, p < 0.001. Analysis of obstetric and gynecologic anamnesis revealed no statistically significant differences in the incidence of gynecologic pathology in the study groups. However, according to the detailed analysis of the delivery history of the participants, 23 patients of the main group (76 %) and 3 patients (6.6 %) of the control group underwent episiotomy during labor, p < 0.001. The evaluation of the comparison groups in terms of pain component in myofascial syndrome involved the pain rating index, number of selected descriptors, sensory index of the selected descriptors, emotional index of the selected descriptors, and pain intensity. Statistically significant differences were revealed for all of the above indicators, thereby confirming a reliable picture of pathopsychological changes in the compared groups of women. The analysis of the ultrasound parameters of topographic and anatomical relationships demonstrated the relevant change in the following parameters: urethral length, diameter of the external urethral sphincter, angle between the external urethra and the body of the bladder, direct and transverse dimensions of the levator hiatus in the studied groups under the muscle tension.Conclusion. An issue of early diagnosis and prophylaxis of chronic pelvic pain syndrome in women of reproductive age remains urgent and requires interdisciplinary participation of medical specialists. The development of new approaches to ultrasound evaluation of pelvic floor will increase the effectiveness of therapeutic and prophylactic measures and reduce the economic burden of this nosology in the morbidity structure of the able-bodied female population.